INFORMATION SUPPORT AND TEACHERS’ EXPERIENCE DURING DISTANCE LEARNING - Temirkhanova М.С.; Abildinova Г.М.; Kazhiakparova Ж.С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
Due to the pandemic caused by the spread of the COVID-19 virus, the country’s educational system has undergone significant changes. The participants of the educational process faced significant problems and completely new experiences. Relevance of the research - innovations in education introduced due to the pandemic have revealed new problems and solutions. At the beginning of distance learning, it was difficult for teachers to learn and implement appropriate methods for this format of learning due to insufficient assistance in the learning process, training or resources. The purpose of the research, based on the theoretical study of the meaning of distance learning and research, as well as finding out the state of teachers during distance learning, is to describe the experience of schools in Kazakhstan during quarantine. The methodology of the study is based on a survey of teachers and analysis. The research highlights the problems in the distance learning format and makes a significant contribution to further research. Analyzing the results of the research and the survey, it was concluded that teachers experienced psycho-emotional and physiological stress due to distance learning. The result showed that the content and form of distance learning is important, the methodological recommendation for the organization of distance learning requires revision.